2008
DOI: 10.1111/j.1369-6866.2004.00314.x-i1
|View full text |Cite
|
Sign up to set email alerts
|

Self-directed learning readiness as an antecedent of organizational commitment: a Korean study

Abstract: This study was to test whether employees possessing a higher level of self‐directed learning (SDL) readiness have significantly stronger organizational commitment in Korean business settings. Job position and length of service in the workplace, which were previously found as related variables to influence organizational commitment, were included to see how strongly they are associated with organizational commitment. This study found that SDL readiness was a meaningful variable in terms of predicting both affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
1
16
1
1
Order By: Relevance
“…In terms of construct validity issues, however, affective commitment is the most widely studied, as it has consistent relationships with organizational outcomes such as performance, attendance, and retention (Meyer and Allen 1997). In particular, the reliability estimate was found to be remarkably similar to those of studies that were using the Korean version of the Affective Commitment Scale: Cronbach's alpha = .87 (Cho and Kwon 2005), .84 (Lee et al 2001), and .86 (Jung 2000), respectively.…”
Section: Affective Organizational Commitmentsupporting
confidence: 61%
See 3 more Smart Citations
“…In terms of construct validity issues, however, affective commitment is the most widely studied, as it has consistent relationships with organizational outcomes such as performance, attendance, and retention (Meyer and Allen 1997). In particular, the reliability estimate was found to be remarkably similar to those of studies that were using the Korean version of the Affective Commitment Scale: Cronbach's alpha = .87 (Cho and Kwon 2005), .84 (Lee et al 2001), and .86 (Jung 2000), respectively.…”
Section: Affective Organizational Commitmentsupporting
confidence: 61%
“…Some studies have focused on its relationship to workplace learning (Cho and Kwon 2005). Consistently, findings have shown that participation in training programs provided by an organization enhances participants' organizational commitment.…”
Section: Organizational Commitmentmentioning
confidence: 96%
See 2 more Smart Citations
“…While there has been a fair amount of empirical investigation of self-directed learning, the research that bears on self-directed learning as a personality trait has been somewhat piecemeal and fragmented. To illustrate, self-directed learning readiness (which includes initiative in learning, acceptance of responsibility for one's own learning, and seeing one's self as an effective independent learner) has been found to be positively related to creative achievements (Torrance & Mourad, 1978); self-concept and years of education (Sabbaghian, 1980); student participation in learning projects (Hassan, 1982); internal locus of control (Skaggs, 1981;Gardner & Helmes, 1999); life satisfaction of elderly individuals (Gardner & Helmes, 1999) and older adults (Curry, 1983); lower levels of dogmatism (Long & Agyekum, 1983); end of year grades of nursing students (Crook, 1985) occupational categories (Durr, Guglielmino, & Guglielmino, 1996); affective organizational commitment (Cho & Kwon, 2005); and intrinsic learning motivation (Reynolds, 1986). Also, a few studies have examined the validity of Oddi's (1984Oddi's ( , 1985Oddi's ( , 1986 Continuing Learning Inventory (CLI)-which includes proactive drive to learn without obvious external reinforcement and commitment to learning for its own sake-with non-definitive results.…”
mentioning
confidence: 97%